2007
DOI: 10.1080/00016340701505002
|View full text |Cite
|
Sign up to set email alerts
|

One or two day mifepristone–misoprostol interval for second trimester abortion

Abstract: The combined regimen of mifepristone and misoprostol is effective in the second trimester, and the interval between the drugs can be reduced allowing individualised patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
4
16
0
1
Order By: Relevance
“…All published studies reported no increase in adverse events, which is in agreement with our findings [13,14,15,16,17]. We report one uterine rupture in a woman with previous caesarean section; no cases have been reported in cohorts with mifepristone-to-misoprostol intervals of <36 h. However, in the context of a small cohort, it is inappropriate to extrapolate the significance of rare adverse events to the mifepristone-misoprostol regimen used.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…All published studies reported no increase in adverse events, which is in agreement with our findings [13,14,15,16,17]. We report one uterine rupture in a woman with previous caesarean section; no cases have been reported in cohorts with mifepristone-to-misoprostol intervals of <36 h. However, in the context of a small cohort, it is inappropriate to extrapolate the significance of rare adverse events to the mifepristone-misoprostol regimen used.…”
Section: Discussionsupporting
confidence: 81%
“…Four RCTs reported percentage expulsion at 12 h post-misoprostol for mifepristone-to-misoprostol intervals <36 h, ranging from 73 to 82% compared to 36.3% in our short regimen cohort [12,13,14,16], although again the mifepristone-to-misoprostol intervals were greater than in our short regimen. Information regarding expulsion at 24 h was provided by 5 of the 6 studies examined and ranged from 91 to 98% [12,14,15,16,17], compared to 80% in our short and 91% in our standard regimen cohorts, respectively. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another randomized trial found that simultaneous use of mifepristone and misoprostol for second trimester medical abortion was not as effective as the 36 to 38-hour dosing interval [4]. In addition, two studies compared the effects of 1-day and 2-day intervals for second trimester pregnancy termination [5,6]. Successful abortion rates were similar between the groups, but the time between misoprostol administration and fetal expulsion was longer in the 1-day group compared with in the 2-day group.…”
Section: Introductionmentioning
confidence: 97%
“…of receiving misoprostol. [8] Increasing gestational age is also correlated with increased induction time when using mifepristone and misoprostol from 12 to 20 weeks. In our study too women with gestational age <16 weeks had a lower (8.5±.8hrs.)…”
Section: Discussionmentioning
confidence: 99%